1987
DOI: 10.1038/hdy.1987.18
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome weights and measures in Petunia

Abstract: The 2C nuclear DNA amounts in diploid Petunia species are low, ranging from 173 to 3OO picograms. The nuclear dry mass and the total chromosome volume are closely correlated with the nuclear DNA amount. So also is cell size measured in pollen grains. Increase in the total nuclear DNA within the genus is achieved by the addition of equal increments of DNA to all members of the chromosome complement irrespective of their size. It is suggested that the correlations and distribution patterns of DNA changes display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(6 reference statements)
2
7
0
Order By: Relevance
“…The resulting high-quality assemblies have a size of 1.26 Gb for P. axillaris and 1.29 Gb for P. inflata (Table 1). The estimated size of both genomes is 1.4 Gb, using a k-mer size of 31, which is consistent with previous microdensity measurements 9 . We have remapped Illumina reads to the assemblies and called single nucleotide polymorphism (SNPs) to estimate the level of heterozygosity, which is estimated as 0.03% for both accessions.…”
Section: Resultssupporting
confidence: 77%
“…The resulting high-quality assemblies have a size of 1.26 Gb for P. axillaris and 1.29 Gb for P. inflata (Table 1). The estimated size of both genomes is 1.4 Gb, using a k-mer size of 31, which is consistent with previous microdensity measurements 9 . We have remapped Illumina reads to the assemblies and called single nucleotide polymorphism (SNPs) to estimate the level of heterozygosity, which is estimated as 0.03% for both accessions.…”
Section: Resultssupporting
confidence: 77%
“…In addition, nuclear DNA content of C. parvi¯ora obtained in the present study (1 . 91 pg) was comparable with that reported by White and Rees (1987) (1 . 71 pg) as mentioned earlier.…”
Section: Chromosome Numbersupporting
confidence: 81%
“…9 pg (FMD; Bennett et al, 1982), 2 . 73 pg (FMD; White and Rees, 1987) and 2 . 64 pg (FCM; Arumuganathan and Earle, 1991).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Provided that the nuclear DNA content is proportional to the nuclear volume and the nuclear volume to the cell volume, endopolyploidization cycles could speed up growth (and development) and compensate for small genome size by saving time, energy and material required for mitotic division. some area, chromosome length and DNA content of 12 diploid rice species (Uozo et al, 1997), between the total volume of centromeres per nucleus and the C-value Leitch, 2004, 2005), between nuclear dry mass and DNA content of Petunia species (White and Rees, 1987) and between rRNA gene copy number and DNA content across a wide range of plant taxa (Prokopowich et al, 2003), were also reported. Furthermore, it was assumed that in eukaryotes the initiation of DNA replication and subsequent cell division depends on the attainment of a critical cell volume (Fantes et al, 1976).…”
mentioning
confidence: 99%